WAYS TO PROTECT PERSONAL DATA ON THE INTERNET - Plotnikova , Т.Г. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2020)
Currently, the protection of personal data is very relevant, although people have been collecting and processing personal information for a long time. Companies declare confidentiality and anonymization of the data collected, but the question arises as to why this data is collected, how much it is protected. Now the conversion of various databases into electronic form simplifies not only legal manipulations with personal data, but also illegal, it has become easier to gain unauthorized access to a large amount of data. There are many risks that personal data will reach those who should not have it. There are various ways to protect personal data, through which users can restrict the access of strangers to personal data. The article discusses various tools that are used to organize comprehensive protection of personal data on the Internet